Enhanced removal of methanethiol and its conversion products in the presence of methane in biofilters. (1st April 2019) - Yao, Xing-Zhi; Chu, Yi-Xuan; Wang, Chen; Li, Hua-Jun; Kang, Ya-Ru; He, Ruo
Abstract: Odors are produced from the treatment and degradation of solid organic waste and seriously affect ecological environments and human health. Control and abatement of volatile sulfur compounds have been identified as critical tasks for maintaining air quality during the treatment and degradation of solid organic waste. Biofiltration is widely used in various applications and is generally known as the least expensive odor treatment technology, but the removal efficiency of organic sulfur compounds is low and variable in biofilters. In this study, the influence mechanism of CH4 on methanethiol removal in biofilters was investigated. Compared with a biofilter containing CH4 and methanethiol (MC biofilter), the removal efficiency of methanethiol in the biofilter only with the input of methanethiol (M biofilter) was lower. The emission rate of methanethiol was 22.8–30.2 mg m −2 d −1 in the M biofilter, which was approximately 2.5 times of that in the MC biofilter. In addition to methanethiol, dimethyl sulfide and dimethyl disulfide were also detected in the biofilters during the experiment. SO4 2− was the primary product of the conversion of methanethiol in the biofilters. Cloning and Miseq sequencing showed that Thiobacillus and Methylobacter spp. were the predominant methanethiol-degrading bacteria in the biofilters. However, most of the mto X clones belonged to novel methanethiol-degrading bacteria in the biofilters. These findings illustrate that the presence of CH4 could enhance methanethiol removal in the biofilter, likely because certain methanotrophs such as Methylobacter spp. had methanethiol oxidase and could oxidize methanethiol to formaldehyde, hydrogen peroxide and hydrogen sulfide, the latter of which was further oxidized to SO4 2− . Graphical abstract: Image 1 Highlights: Certain methanotrophs have methanethiol oxidase and can oxidize methanethiol. SO4 2- -S was the main product of the conversion of methanethiol-S. Dimethylsulfide and dimethyl disulfide generated from methanethiol conversion. CH4 could enhance the removal of MT and its conversion product (e.g. DMDS). Greater change of microbial community occurred in the presence of CH4 .